2019
DOI: 10.1136/bmjopen-2018-027207
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of sofosbuvir as treatment for yellow fever: protocol for a randomised controlled trial in Brazil (SOFFA study)

Abstract: IntroductionAn ongoing outbreak of yellow fever (YF) has been reported in Brazil with 1261 confirmed cases and 409 deaths since July 2017. To date, there is no specific treatment available for YF. Recently published papers describing in vitro and animal models suggest a potential effect of antiviral drugs (approved for the treatment of hepatitis virus) against flaviviruses, including YF. The primary aim of this study is to analyse the effect of sofosbuvir on viral kinetics and clinical outcomes among patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
6
0
3
Order By: Relevance
“…This approach proved feasible for combating the Zika, yellow fever and chikungunya outbreaks experienced in Brazil over the past 5 years, when our group demonstrated that sofosbuvir, a blockbuster drug against hepatitis C, could represent a compassionate countermeasure against these diseases (25)(26)(27)(28)(29).…”
Section: ) Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This approach proved feasible for combating the Zika, yellow fever and chikungunya outbreaks experienced in Brazil over the past 5 years, when our group demonstrated that sofosbuvir, a blockbuster drug against hepatitis C, could represent a compassionate countermeasure against these diseases (25)(26)(27)(28)(29).…”
Section: ) Discussionmentioning
confidence: 98%
“…Preclinical data on the susceptibility of an emerging virus to clinically approved drugs can allow for the rapid mobilization of resources toward clinical trials ( 8 ). This approach proved feasible for combating the Zika, yellow fever, and chikungunya outbreaks experienced in Brazil over the past 5 years, when our group demonstrated that sofosbuvir, a blockbuster drug against hepatitis C, could represent a compassionate countermeasure against these diseases ( 25 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…To rapidly respond to unfolding pandemics, the cataloguing of preclinical data on susceptibility of SARS-CoV-2 to approved drugs is of paramount importance, and provides opportunities for rational selection of promising products for evaluation in clinical trials [37]. The investigators used this approach during ZIKV, YFV, and CHIKV outbreak in Brazil, and demonstrated susceptibility of these viruses to SFV [1316,38]. SFV and DCV are considered safe and well tolerated anti-HCV therapies that are orally bioavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many attempts to develop an effective treatment for yellow fever, including other nucleoside analogs [3,10,11,14], no compound has successfully demonstrated efficacy against the disease in human testing. Sofosbuvir, a clinically approved drug against hepatitis C virus (HCV), has recently been shown to inhibit YFV in vitro and in vivo [2,8], and a clinical trial in Brazil to test its efficacy in humans infected with YFV is currently underway [16]. AT-752 has also been shown to be a potent inhibitor of HCV [12], as is its congener AT-527 which forms the same active triphosphate, and was up to 58-fold more potent than sofosbuvir against HCV clinical isolates [13].…”
mentioning
confidence: 99%